PAIKEM APPLICATION ON PROCLAMATION APPROACH OF INDONESIA’S INDEPENDENCE MATERIAL (TO INCREASE STUDY ACTIVITY AND RESULT) - Siti Halimatus Sakdiyah; Harun Harun (STKIP Singkawang, 2017)
This article is proposed to increase activity and study result student of IPS subject On Proclamation Approach of Indonesia’s Independence material. PAIKEM is one of active learning, innovative, creative, effective, and enjoyable. This research is Classroom Action Research (PTK) with qualitative that is done by two cycles. The kinds of data is direct data from research subject that is student of VI grade SDN Kebonsari 4 Malang. The amount is 40 students. The material of this research is “Proclamation Approach of Indonesia’s Independence”. The data collections are used observation sheet, field note, and documentation. The result of this research describe that PAIKEM increase study activity of student, this is shown from the student score on student activity instrument. On the I cycle score value is average 75% with good enough criteria, while on the II cycle score value is average 86% with good criteria. This is shown that there is improvement of student activity. Besides that, PAIKEM also increase student activity and creativity of the study result. The study result of student is increase as long as the first cycle with average score 83%and in the last on the second cycle with average score 89%. So, it can be concluded that PAIKEM application is able to increase activity and study result of student VI grade SDN Kebonsari 4 Malang.